The Threshold Effect of Two-way FDI on Environmental Pollution Under Environmental Regulation - Yang, Kaijun; Wang, Chan; Wen, Yuanyuan; Mao, Xianqiang (Journal of Environmental Accounting and Management, 2026)
Based on the data of 11 provinces or cities in the Yangtze River Economic Zone from the year of 2006 to 2015,through constructing the panel threshold model, this paper analyzed the threshold effect of the two-way FDI on the upgrading of industrial structure and environment on different levels of environmental regulation. The results show that two-way FDI can effectively reduce environmental pollution, while the emission reduction effects are significantly different under different environmental regulations, too loose or too strict environmental constraints would inhibit the technical spillover effect of IFDI and the reversely technological spillover effect of OFDI, thus the environmental improvement effect cannot be fully played. In summary, only with appropriate environmental regulations, twoway FDI can promote the upgrading of the overall industrial structure of the Yangtze River economic belt, maximize its emission reduction effect at the same time, thus achieve the dual goals of economic development and environmental protection in the Yangtze River Economic Zone.